2021
DOI: 10.3389/fonc.2021.712950
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiomic Features in a Diverse Cohort of Patients With Pancreatic Ductal Adenocarcinomas

Abstract: BackgroundSignificant racial disparities in pancreatic cancer incidence and mortality rates exist, with the highest rates in African Americans compared to Non-Hispanic Whites and Hispanic/Latinx populations. Computer-derived quantitative imaging or “radiomic” features may serve as non-invasive surrogates for underlying biological factors and heterogeneity that characterize pancreatic tumors from African Americans, yet studies are lacking in this area. The objective of this pilot study was to determine if the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The participants in our internal dataset were entirely Asian patients, and the external dataset consisted of two different open-source datasets from the United States. The pancreatic content is one of the major factors influencing race/ethnicity differences [ 16 , 48 , 49 ]. Furthermore, diverse scanners at different institutions may also decrease sensitivity and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The participants in our internal dataset were entirely Asian patients, and the external dataset consisted of two different open-source datasets from the United States. The pancreatic content is one of the major factors influencing race/ethnicity differences [ 16 , 48 , 49 ]. Furthermore, diverse scanners at different institutions may also decrease sensitivity and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In distinguishing between high and low mesothelin expression in pancreatic cancer, it may imply that regions with high mesothelin expression have more textural diversity or grey level variation in the image, different from tissues with low mesothelin expression. An interesting nding [30] revealed that patients with higher GLCM values in the imaging histological features of pancreatic cancer had lower survival rates in different populations. This implies that radiological features are expected to be a surrogate for underlying biological factors that predict clinical outcomes, adding predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing radiomics features in diverse populations with pancreatic ductal adenocarcinoma (PDAC) identified several textural radiomics features associated with unfavorable outcomes among Black patients with PDAC, independent of other prognostic factors such as tumor grade. The analytic dataset included cross sectional radiographs for 71 patients treated at a single institution [62].…”
Section: Radiomicsmentioning
confidence: 99%